(3aYGdjI HQfGeL JOQjHj ebJQM HGSJNOGe GdGdYGH GdTHg QjGVjI aj JfejI bOQI GdGfJHGg h NaV aQW GdMQcI dPhj UYhHGJ GdJYde (B: (3HMK GLQj HeQcR GdJcja GdeOQSj HHf Ycfhf aFI (B06 - 09 (3SfhGJ s - (3Hf SYjO , eMeO GdGejfs; (3HdZhd, aJMjs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2021)
(3edNU GdOQGSI (B:(3JeKdJ GgOGa GdOQGSI aj GdJYQa Ydi aYGdjI HQfGeL JOQjHj ebJQM HGSJNOGe GdCdYGH GdTHg QjGVjI aj JfejI bOQI GdGfJHGg hNaV aQW GdMQcI dPhj UYhHGJ GdJYde ef Phj UYhHGJ GdbQGAI hGdcJGHI hGdMSGH, MjK CLQjJ GdOQGSI HeQcR GdJcja GdeOQSj HHf Ycfhf ddaFI GdYeQjI (B6-9 (3SfhGJ, hdJMbjb CgOGa GdOQGSI GSJNOe GdHGMK GdefgL GdJLQjHj,Ydi YjfI JYOGOgG (B24 (3Wad(B(12 (3JejP aj GdYjfI GdJLQjHjI, h(B12 (3Wad aj GdYjfI GdTGgOI(B)(3, MjK jJeR gDdGA GdCWaGd HVYa GdGfJHGg haQW MQcj, dPG gOaJ GdOQGSI Gdi eMGhdI JfejI egGQGJ GdGfJHGg hNaV aQW GdMQcI ef NdGd HQfGeL GdYGH MQcjI, hGSJYGf GdHGMK HLedI ef GdebGjjS hGdGNJHGQGJ JeKdJ aj ebjGS GdGfJHGg haQW GdMQcI ddOcJhQI SfGA eMeO SdjeGf, HGdEVGaI Gdi GdGNJHGQGJ GdJMUjdjI aj GdehGO GdOQGSjI, dOQGSI GKQ GdHQfGeL Ydi UYhHGJ GdJYde, hHYO GdeYGdLI GdEMUGFjI JhUd GdHGMK Gdi Gf dHQfGeL GdCdYGH GdTHg QjGVjI aYGdjI aj JfejI bOQI GdGfJHGg h VHW Sdhc aQW GdMQcI, HGdEVGaI Gdi GKQ GjLGHj aj JfejI GdegGQGJ GdCcGOjejI (B((3GdbQGAI, GdMSGH, GdcJGHI(B)(3, hHfGAG Ydi eG JhUd Gdjg GdHGMK ef fJGFL ,ChUi HVQhQI GdGfJbGd Gdi adSaI GdJYde HGddYH, hCgejI GYJeGO MUU GdJQHjI GdMQcjI aj GdefGgL GdJQHhjI(B. s
(3OcJhQGIs
Keywords: (3GdGVWQGHGJ GdSdhcjIs; (3GdGdYGH GdTHg QjGVjIs; (3GdfTGW GdHOfj GdQjGVj GdeOQSjs; (3Yde GdMQcIs